2009
DOI: 10.1111/j.1540-8175.2008.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Function Study with Conventional and Pulsed Tissue Doppler Echocardiography Imaging in Acromegalic Patients

Abstract: In this study, DC and TDI were equally effective in demonstrating diastolic dysfunction, a common finding in acromegalic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…16 Previous studies demonstrated negative effects of LV hypertrophy on LV functions by conventional and tissue Doppler echocardiography in various circumstances. [17][18][19] In addition, a positive and significant correlation of increased LV mass with myocardial dysfunction was demonstrated in the literature. 20,21 Based on these data, an increased LV mass may contribute to impaired MPI in patients with PV.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…16 Previous studies demonstrated negative effects of LV hypertrophy on LV functions by conventional and tissue Doppler echocardiography in various circumstances. [17][18][19] In addition, a positive and significant correlation of increased LV mass with myocardial dysfunction was demonstrated in the literature. 20,21 Based on these data, an increased LV mass may contribute to impaired MPI in patients with PV.…”
Section: Discussionmentioning
confidence: 86%
“…Also, LV hypertrophy was related to increased total plasma volume in patients with PV 16 . Previous studies demonstrated negative effects of LV hypertrophy on LV functions by conventional and tissue Doppler echocardiography in various circumstances 17–19 . In addition, a positive and significant correlation of increased LV mass with myocardial dysfunction was demonstrated in the literature 20,21 .…”
Section: Discussionmentioning
confidence: 88%
“…A normal EF was found in all patients studied, including those with active and inactive acromegaly. Normal systolic function in acromegalic patients has also been reported in other studies [21].…”
Section: Discussionmentioning
confidence: 58%
“…A previous study, which used only the Em/Am ratio as pwTDI, suggested conventional (E/A) and pwTDI techniques are equally effective in demonstrating LVDD. 18) On the contrary, we found a reduced ratio of LVDD by using new criteria based on the E/Em ratio. We think that previous studies might have overestimated the prevalence of LVDD by using old methods.…”
Section: Discussionmentioning
confidence: 64%